Implementasi Algoritme Lizard untuk Pengamanan Protokol MQTT pada Perangkat NodeMCU - Rizal Dismantoro; Ari Kusyanti; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The Message Queuing Telemetry Protocol (MQTT) protocol is one of the IoT protocol which has a mechanism based on topic-based publish-subscribed systems that have properties that are suitable to be implemented on devices that have limited resources. This is due to it has light-weight properties. MQTT is one of the protocols that is often used on IoT, but there are several weaknesses in the security issues. To ensure the data security an algorithm is needed to encrypt data. One of security algorithm for encrypting data is the Lightweight Stream Cipher for Power-constrained Devices (Lizard) algorithm. In the publisher section before the message is sent it will be encrypted (ciphertext). In broker the ciphertext will forward to the subscriber. In the subscriber, the message will be decrypted. Based on the test results, the Lizard algorithm implemented in the MQTT protocol successfully secure a system on NodeMCU device that take 1014419 microsecond.